2019
DOI: 10.1038/s41598-019-49045-9
|View full text |Cite
|
Sign up to set email alerts
|

Combined pharmacological administration of AQP1 ion channel blocker AqB011 and water channel blocker Bacopaside II amplifies inhibition of colon cancer cell migration

Abstract: Aquaporin-1 (AQP1) has been proposed as a dual water and cation channel that when upregulated in cancers enhances cell migration rates; however, the mechanism remains unknown. Previous work identified AqB011 as an inhibitor of the gated human AQP1 cation conductance, and bacopaside II as a blocker of AQP1 water pores. In two colorectal adenocarcinoma cell lines, high levels of AQP1 transcript were confirmed in HT29, and low levels in SW480 cells, by quantitative PCR (polymerase chain reaction). Comparable diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 76 publications
(86 reference statements)
1
24
0
Order By: Relevance
“…The attenuation of HT-29 cell migration in monotherapy has been demonstrated as well as a significant improvement of this process in combined therapy. Moreover, a decreased invasiveness of cells was observed after bacopaside II treatment [191]. A similar effect was demonstrated in colon cancer cells (HCT116, SW480) after AQP-5 knock-down with specific shRNA [192] .…”
Section: Carcinogenesis Modulators: From Basic Research To Clinical Psupporting
confidence: 69%
“…The attenuation of HT-29 cell migration in monotherapy has been demonstrated as well as a significant improvement of this process in combined therapy. Moreover, a decreased invasiveness of cells was observed after bacopaside II treatment [191]. A similar effect was demonstrated in colon cancer cells (HCT116, SW480) after AQP-5 knock-down with specific shRNA [192] .…”
Section: Carcinogenesis Modulators: From Basic Research To Clinical Psupporting
confidence: 69%
“…Effects on motility could arise from AQP1-associated effects on actin organization via RhoA and Rac signaling pathways [ 123 ]. Alternatively, the role of AQP1 in colon cancer might depend on a dual water and ion channel function suggested to promote lamellipodial extension and cell migration [ 5 , 12 , 123 ]. AQP5 similarly has been proposed as a prognostic biomarker for colorectal cancer, with AQP5 levels found to be proportional to numbers of circulating tumors cells [ 124 , 125 , 126 ] and risk of liver metastases [ 126 ].…”
Section: Resultsmentioning
confidence: 99%
“…This reliance on an AQP subtype indicates that the tumorigenic roles are unlikely to stem simply from increasing water channel activity and osmotic water flux, but must be exploiting features such as substrate permeability, mechanisms of regulation, subcellular localization or other properties that differ between subtypes. AQPs have been proposed to promote cancer metastasis by facilitating tumor cell migration [ 6 , 7 , 12 ], but a broader range of possible functions is likely, given the expanding understanding of their diverse roles in normal cell physiology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, an interesting finding has been reported recently by De Leso et al where it was observed that the blockers AqB011 and bacopaside II exhibit synergistic action, amplifying the inhibition of 2D cell migration in two colon cancer cell lines [ 132 ].…”
Section: Natural Health Products and Natural Compounds Used In Thementioning
confidence: 87%